Content validity of agility test in karate kumite category - Yudhistira, D.; Tomoliyus (International Journal of Human Movement and Sports Sciences, 2020)
Background: Kumite is a category in karate match. It is a one-on-one match that requires complex physical aspects, one of which is physical agility. In a real match, kumite requires movements to shift the direction quickly when a karateka aims to hit his opponent. For that reason, there should be a program and an assessment to improve the physical agility of the karate athletes who compete in kumite category. The document analysis of this research found that there has not been any assessment tool for the agility aspect in kumite, while the existing agility test measuring tool was only designed for sports in general. Purpose: This research aimed to develop the construction of karate agility test for the kumite category. Design/methodology/approach: This is a developmental research which consisted of 3 stages. In the first stage, documents and research journals were analyzed to develop the construction of karate agility test for the kumite category. In the second stage, the Delphi technique was utilized and the experts were asked to assess he construction of karate agility test for the kumite category resulted in the first stage. In the third stage, the results of expert judgment with the Aiken formula were analyzed to test the content validity. The participants in this research were documents and seven experts. Results: It was found in the construction of the Kumite category karate agility test; item one, the content or material got a V value of 0.85; item two, the distance between the cone had a V value of 0.95; item three, the safety of the equipment used has a V value of 0.90; item four, the number of test replications had a V value of 0.90; item five, the clarity of the test procedure had a V value of 0.90; items six, the clarity of the test score had a V value of 0.90. Conclusion: The karate agility test construction for the kumite category had high content validity.